ANALYSIS OF CARBON DIOXIDE EMISSIONS AND REMOVALS IN BRAZILIAN BIOMES FROM 1990 TO 2023 (REMUNOM, 2026)
Brazil is covered by six biomes with vast biodiversity, predominantly native vegetation and forest formations. These are: Amazon, Caatinga, Cerrado, Atlantic Forest, Pampa, and Pantanal. Different changes in land use and forests directly influence the increase or decrease of carbon dioxide (CO2). Using CO2 emissions and removals data from 1990 to 2023, available from the SEEG platform (System for Estimating Emissions and Removals of Greenhouse Gases), it was possible to evaluate patterns of behavior of these important measures during this period. For both emissions and removals, the biomes showed, according to the Mann-Kendall test, a significant decreasing trend, despite the fluctuations observed during the period. The Caatinga was the only biome that recorded negative net emissions in some years, implying that removals exceeded emissions. However, it is necessary to highlight the growth in emissions in the most recent years in this biome and the Pantanal. Clustering using the k-means method identified similarities between biomes, isolating the Amazon and grouping the others together. Cerrado and Atlantic Forest were grouped together in one category, and Caatinga, Pampa, and Pantanal together in another for emissions. In the case of removals, Caatinga, Cerrado, and Atlantic Forest formed one group, and Pampa and Pantanal formed a third group. The results offer important insights to guide conservation strategies and more effective public policies in addressing climate change.